A Nonlinear Schrödinger Model for Many-Particle Quantum Systems. (22nd October 2012) - Zhang, Qiang; Ma, Tian
Abstract : Considering both effects of the s-wave scattering and the atom-atom interaction rather than only the effect of the s-wave scattering, we establish a nonlinear Schrödinger model for many-particle quantum systems and we prove the global existence of a solution to the model and obtain the expression of the solution. Furthermore, we show that the Hamilton energy and the total particle number both are conservative quantities.